2013
DOI: 10.4236/wjcs.2013.32005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Right Internal Jugular Vein Cross-Sectional Area Change in Response to Trendelenburg Positioning

Abstract: Background/Purpose: The right internal jugular vein (RIJV) is the most commonly accessed central venous site in the cardiac operating room. The Trendelenburg position is frequently used to increase the cross-sectional area (CSA) of the RIJV to facilitate its cannulation. However, the extent of change of RIJV CSA in response to Trendelenburg positioning in anesthetized patients and its predictive factors remain unknown. Methods: Thirty-seven patients presented for the cardiac surgery, and 20 ASA I and II surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…All of the patients were positioned with their neck in extension and head rotated left at [20][21][22][23][24][25][26][27][28][29][30] . Patients were studied in State 0, table flat (no tilt), with the patients in the supine position, and State T, in which the operating table was tilted 15 to a TP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the patients were positioned with their neck in extension and head rotated left at [20][21][22][23][24][25][26][27][28][29][30] . Patients were studied in State 0, table flat (no tilt), with the patients in the supine position, and State T, in which the operating table was tilted 15 to a TP.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings were reported in another study conducted by Modeliar et al 24 who found that the TP increased the mean CSA by only 15% in 60 ICU patients. Maratea et al 28 evaluated the extent of change of the CSA of the right IJV in response to TP in anesthetized patients and its predictive factors. They showed that right IJV dilation in response to TP was only significantly different in male patients.…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation